You are on page 1of 14

ECE 307

Fourier Transform

Z. Aliyazicioglu
Electrical & Computer Engineering Dept.
Cal Poly Pomona

Fourier Transform
The Fourier transform (FT) is the extension of the Fourier series to
nonperiodic signals. The Fourier transform of a signal exist if
satisfies the following condition.

2


x(t ) dt <

x(t )e
j t
The Fourier transform X ( ) = dt

The inverse Fourier transform (IFT) of X() is x(t)and given by



1
X ( )e
j t
x(t ) = d
2

1
Fourier Transform
Also, The Fourier transform can be defined in terms of frequency of
Hertz as

x(t )e
j 2 ft
X (f ) = dt

and corresponding inverse Fourier transform is

X (f )e
j 2 ft
x(t ) = df

Fourier Transform
Example: Determine the Fourier transform of a rectangular pulse
shown in the following figure
x(t)

h a/2
j 2a
h j
a

X ( ) =
a / 2
he jt dt =
e
j
e 2

t
-a/2 a/2 a
2h a sin( )
= sin( ) = ha 2
2 a
2
a
= ha sinc
2

2
Fourier Transform
Example: To find in frequency domain,
a/2
j 22fa
h j
2 fa

X (f ) =
a / 2
he j 2 ft dt = e
j 2 f
e 2

h = 1,
h sin( fa)
= sin( fa) = ha a =1
f fa

= ha sinc ( fa ) X ( ) = 2sinc
2

>> h=1;
>> a=1;
>> f=-3.5:0.01:3.5;
>> w=2*pi*f;
>> x=h*a*sinc(w*a/(2*pi));
>> plot (w,x)
>> title ('X(\omega)')
>> xlabel('\omega');
>>

Fourier Transform

h = 1,
a=2
2
X ( ) = 2sinc
2

>> h=1;
>> a=1;
>> f=-3.5:0.01:3.5;
>> w=2*pi*f;
>> x=abs(h*a*sinc(w*a/(2*pi)));
>> subplot (2,1,1)
>> plot (w,x)
>> title ('|X(\omega)|')
>> xlabel('\omega')
>> xp=phase(h*a*sinc(w*a/(2*pi)));
>> subplot (2,1,2)
>> plot (w,xp)
>> title ('phase X(\omega)')
>> xlabel('\omega')

3
Fourier Transform
Example

Determine the Fourier transform of the Delta function (t)

(t )e
j t
X ( ) = dt = e j 0 = 1

X()
1

Fourier Transform
Properties of the Fourier Transform
We summarize several important properties of the Fourier Transform as follows.

1. Linearity (Superposition)

If x1(t ) X 1( ) and x2 (t ) X 2 ( )

Then, a1x1(t ) + a2 x2 (t ) a1X1( ) + a2 X 2 ( )

Proof:

[a1x1(t ) + a2 x2 (t )] e dt = a1 x1(t )e dt + a2 x2 (t )e dt
j t j t j t

= a1X 1( ) + a2 X 2 ( )

4
Fourier Transform
Properties of the Fourier Transform

2. Time Shifting

If x(t ) X ( )

Then, x(t t0 ) X ( )e jt0

Proof: Let = t t0 then t = + t0 and dt = d


x( )e
j ( +t0 )
x(t t0 )e jt dt = d


= e j t 0 x( )e
j
d

= e jt0 X ( )

Fourier Transform

Let y (t ) = x(t t0 )

Y ( ) = X ( )e jt0 = X ( ) e j X ( )e jt0
= X ( ) e j ( X ( )t0 )

Y ( ) e j Y ( ) = X ( ) e j ( X ( )t0 )

Therefore, the amplitude spectrum of the time shifted signal is the


same as the amplitude spectrum of the original signal, and the phase
spectrum of the time-shifted signal is the sum of the phase spectrum of
the original signal and a linear phase term.

5
Fourier Transform
Example: Determine the Fourier transform of the following time
shifted rectangular pulse.
x(t)

a j 2
h a
X ( ) = ha sinc e
t
2
0 a
>> h=1;
>> a=1;
>> f=-3.5:0.01:3.5;
>> w=2*pi*f;
>> x=abs(h*a*sinc(w*a/(2*pi)).*exp(-
j*w*1/2));
>> subplot (2,1,1)
>> plot (w,x)
>> title ('|X(\omega)|')
>> xlabel('\omega')
>> xp=phase(h*a*sinc(w*a/(2*pi)).*exp(-
j*w.*1/2));
>> subplot (2,1,2)
>> plot (w,xp)
>> xlabel('\omega')
>> title ('phaseX(\omega)')

Fourier Transform
3. Time Scaling

If x(t ) X ( ) then
1
x(at ) X( )
a a

Proof: Let = at then t = / a and dt = (1/ a)d

If , a>0 then If , a<0 then



j 1
j 1
x(at )e x( )e
j t
dt = a
d x(at )e
j t
dt = x( )e a
d

a
a
1

1 j 1
= X( )
a a
=
a x( )e

a
d =
a
X( )
a

6
Fourier Transform
Example. if , x(t ) X ( ) then find the Fourier transform of the
following signals
1
a. x( 2t ) X( )
2 2
b. x(t / 5) 5 X (5 )
1 j 2
c. x( 5(t 2)) X ( )e
5 5

Example: Find the Fourier transform of the following signal.


x1(t ) = (t ) X1( ) = sinc
a. 2
1 1
b. x2 (t ) = (5t ) X 2 ( ) = X1( ) = sinc
5 5 5 10

c. x3 (t ) = (t / 5) X 3 ( ) = 5 X1(5 ) = 5sinc
0.4

Fourier Transform
4. Duality (Symmetry)
If x(t ) X ( ) then

X (t ) 2 x( ) or X (t ) x(f )

Proof: Since t and are arbitrary variables in the inverse Fourier


transform

1
X ( )e
j t
x(t ) = d
2

we can replace with t and t with - to get



1 Therefore,
X (t )e
j t
x( ) = dt
2
F {X (t )} = X (t )e
j t
dt = 2 x( )

7
Fourier Transform
Similarly, if we can replace f with t and t with -f in the inverse
Fourier transform

X (f )e
j 2 ft
x(t ) = df

to get

X (t )e
j 2 ft
x( f ) = df

Therefore,

F {X (t )} = x(f )

Fourier Transform
Example: x(t ) = (t ) X ( ) = 1 Applying symmetry property,

x(t ) = 1 X ( ) = 2 ( ) = 2 ( ) ( ( ) is even function)

or x(t ) = 1 X (f ) = (f ) = (f )

Example:
t a
x(t ) = rect X ( ) = a sinc
a
2
ta
x(t ) = a sinc X ( ) = 2 rect a = 2 rect a
2

a
Let c= then a = 2 c
2
1
x(t ) = a sinc ( ct ) X ( ) = 2 rect = c rect 2 c
2 c

8
Fourier Transform
Time Reversal
If x(t ) X ( ) then

x(t ) X ( )

Proof: Let t = . Then t = and dt = d

x( t )e jt dt = x( )e
j ( )
d = X ( )

Fourier Transform
Frequency Shifting
If x(t ) X ( ) then

x(t )e jct X ( c )

Proof:

x(t )e jct e jt dt = x(t )e


j ( c )t
dt = X ( c )

9
Fourier Transform
Example: Determine the Fourier transform of cos ct and sinct

1 j c t 1 j c t
x(t ) = cos ct = e + e X ( ) = [ ( c ) + ( + c )]
2 2

or
1 j c t 1 j c t 1
x(t ) = cos ct =
2
e + e
2
X (f ) =
2
[ (f fc ) + (f + fc )]
X(f)
1/2

-fc fc f

The phase spectrum is zero everywhere.

Fourier Transform
1 j c t 1 j c t
x(t ) = sinct = e e X ( ) = j [ ( c ) ( + c )]
2j 2j

1 j c t 1 j c t j
x(t ) = sinct =
2j
e e
2j
X (f ) =
2
[ (f fc ) (f + fc )]
|X(f)|
1/2

-fc fc f
(f)
/2

fc

-fc f

-/2

10
Fourier Transform
7. Modulation
If x(t ) X ( ) then
1
x(t )cos(ct )
2
[ X ( c ) + X ( + c )]

Proof:

1
x(t )cos( t )e x(t ) 2 e
jc t
c
j t
dt = + e jct e jt dt

1

= x(t )e j ( c )t dt + x(t )e j ( +c )t dt
2
1
=
2
[ X ( c ) + X ( + c )]

Fourier Transform
8. Time Differentiation:
If x(t ) X ( ) then General case

dx(t ) d n x(t )
j X ( ) ( j )n X ( )
dt dt n

Proof: Taking the derivative of the inverse Fourier transform



1
X ( )e
j t
x(t ) = d
2

we obtain dx(t ) 1
dt
=
2
j X ( )e jt d

Therefore dx(t )
j X ( )
dt

11
Fourier Transform
9. Time Differentiation:
If x(t ) X ( ) then General case

dX ( j ) d n X ( )
t n x(t ) j n
tx(t ) j d n
d
Proof: Taking derivative of Fourier Transform

x(t )e
j t
X ( ) = dt with respect to , we obtain


dX ( )
= ( jt ) x(t )e jt dt
d

dX ( j )
Therefore tx(t ) j
d

Fourier Transform
10 Conjugate
If x(t ) X ( ) then

x * (t ) X * ( )

Proof:
*


x (t )e dt = x(t )e j ( )t dt = X * ( )
* j t


If x(t) is real x (t ) = x (t ) so that
*
X ( ) = X * ( )

12
Fourier Transform
11. Convolution

If x(t ) X ( ) ,h(t ) H ( ) , and y (t ) Y ( )



y (t ) = h(t ) * x(t ) = h( )x(t )d

Y ( ) = H ( )X ( )
Proof:


Y ( ) = h( )x(t )d e
jt
dt

Interchanging the order of integration, we obtain



Y ( ) = h( ) x(t )e jt dt d Y ( ) = h( )X ( )e d = X ( ) h( )e d
j j

= X ( )H ( )

Fourier Transform
12. Multiplication

If x1(t ) X1( ), and x2 (t ) X 2 ( )


1 1
x1(t ) x2 (t )
2
X1( ) * X 2 ( ) =
2 X (v )X

1 2 ( v )dv

or

x1(t ) x2 (t ) X 1(f ) * X 2 (f ) = X (v )X

1 2 (f v )dv

13
Fourier Transform
13. Parsevals Theorem

If x1(t ) X1( ), then total normalized(based on one ohms


resistor) energy E of and x(t) is given by

2 1 2 2
E=

x(t ) dt =
2

X ( ) d =

X (f ) df

Proof


2

1

x(t ) 2 X ( )e
j t
x(t ) dt = x(t ) x * (t ) dt = *
d dt

Interchanging the order of integration, we obtain

Fourier Transform

Proof (cont)


2 1


x(t )e dt d
j t
x(t ) dt = X *
( )

2

1
= X ( )X ( )d
*

2

1 2
=
2

X ( ) d

14

You might also like